New strategy towards the assembly of hierarchical heterostructures of SnO2/ZnO for NO2 detection at a ppb level. Issue 10 (29th August 2019) - Xu, Manzhang; Yu, Runwei; Guo, Yuxi; Chen, Cheng; Han, Qingqing; Di, Jun; Song, Pin; Zheng, Lu; Zhang, Zhiyong; Yan, Junfeng; Zhao, Wu; Yun, Jiangni; et al.
Abstract : The SnO2 /ZnO hierarchical heterostructures (HHSs) were synthesized via the microwave-assisted hydrothermal method, and the SnO2 /ZnO HHSs based sensor exhibited ultra-low detection limit of 2 ppb for detecting NO2 . Abstract : Metal oxide hierarchical heterostructures (HHSs) for gas sensors with controllable and novel nanostructures have attracted tremendous attention due to their multi-junction, multi-phase, interfacial and synergic effects. Based on various metal oxide materials, multifarious hierarchical nanostructures and heterostructures can be constructed to enhance the sensor performances of the primary structures. Herein, SnO2 /ZnO HHSs are successfully prepared via a fast, simple, and low-cost microwave-assisted hydrothermal (MWAH) approach. The epitaxial growth of SnO2 nanorods on ZnO nanoflowers formed hierarchical structures that are conducive to promoting sensor performance. The detection limit is 2 ppb for NO2 based on the SnO2 /ZnO HHSs. The sensor response toward 10 ppm NO2 is 52.3, which is 5 and 10 times higher than those of SnO2 and ZnO. The response and recovery times of SnO2 /ZnO HHSs are 16 and 10 s, respectively. We believe that the strategy of synthesizing metal oxides with HHSs based on the MWAH method provides novel insight into the next generation of gas sensors.